Biomateriais compósitos poliméricos - uma opção aos enxertos ósseos - MOREIRA, Islene Silva (2019)
The quest for rehabilitation in dentistry made it necessary to use bone grafts to replace the lost bone. The limitations on the use of natural grafts stimulated the search for synthetic alternatives that approach the most of the human bone properties. A thematic review was conducted using the literature database of PubMed (MEDLINE) assessing the effectiveness of biomaterials based on compounds of bioresorbable polymers combined with calcium phosphate. Studies have shown osteoconduction, stimulation of proliferation and satisfactory mechanical properties. With further research there is the possibility of this biomaterial fulfill the requirements of ideal artificial bone graft, replacing the current bone grafts.